Marketing en las empresas prestadoras de servicios turísticos de Boyacá (2016)
Tourism has become one of the most important economic activities and in someparts of the world is the main source of sustainable economic resources. Thedepartment of Boyaca, has great potential for nature, cultural, historical and health tourism, among others. However, some studies have shown to have serious shortcomings in marketing. This study analyzes the key to improving tourism marketing strategies companies Boyacá elements.